Neutrophilic inflammation and IL-8 levels in induced sputum of alpha-1-antitrypsin PiMZ subjects. Issue 2 (11th November 2005) - Malerba, M; Ricciardolo, F; Radaeli, A; Torregiani, C; Ceriani, L; Mori, E; Bontempelli, M; Tantucci, C; Grassi, V
Abstract : Background: Severe alpha-1-antitrypsin deficiency (AATD), due to homozygosity for the protease inhibitor (Pi) Z allele, is a genetic risk factor for chronic obstructive pulmonary disease (COPD). In a previous study the sputum of severe AATD subjects with airflow obstruction showed a pattern of cellular inflammation similar to COPD patients. It is uncertain whether heterozygotes for the Z allele or intermediate deficiency (PiMZ) have an increased risk of developing COPD. Methods: Sputum cell counts and the supernatant level of the neutrophil chemoattractant interleukin (IL)-8 were investigated by sputum induction in 10 non-smoker asymptomatic PiMZ subjects with normal pulmonary function, 10 patients with stable COPD, and 10 age matched normal subjects. Data are expressed as mean (SD). Results: The mean (SD) number of neutrophils was significantly higher (p<0.01) in the sputum of PiMZ subjects (84.5 (22.2) ×10 4 /ml) and patients with COPD (126.9 (18.8) ×10 4 /ml) than in matched normal subjects (55.0 (8.7) ×10 4 /ml). IL-8 levels were increased in PiMZ subjects (828.5 (490.6) ng/ml; median 1003.0 ng/ml; range 1260–100 ng/ml) and in COPD patients (882.5 (524.3) ng/ml; median 934.9 ng/ml; range 1506–258 mg/ml) compared with normal subjects (3.5 (0.5) ng/ml; median 3.5 ng/ml; range 4.5–2.5 ng/ml). There was a significant positive correlation between IL-8 supernatant concentration and neutrophil count in PiMZ subjects (p = 0.036; r = 0.66). An inverse correlation was observed between the percentage of neutrophils and forced expiratory volume in 1 second (% predicted) in patients with COPD (p = 0.04; r = −0.43). Conclusions: These findings indicate that PiMZ subjects without airflow obstruction may have an IL-8 related neutrophilic inflammation in the airways, similar to stable COPD patients, suggesting an increased risk of developing pulmonary changes.